Green Electronics: Chitin Nanofiber Transparent Paper for Flexible Green Electronics (Adv. Mater. 26/2016). Issue 26 (7th July 2016) - Jin, Jungho; Lee, Daewon; Im, Hyeon‐Gyun; Han, Yun Cheol; Jeong, Eun Gyo; Rolandi, Marco; Choi, Kyung Cheol; Bae, Byeong‐Soo
Abstract : J. Jin, B.‐S. Bae, and co‐workers develop an optically transparent paper made of self‐assembled ultrafine chitin nanofibers (ChNF) and demonstrate its utilization as a substrate for flexible organic light‐emitting diodes. The used squid pen‐derived chitin is the second most abundant biopolymer on earth after cellulose. As described on page 5169, because of the promising macroscopic properties of the ChNF transparent paper, the biofriendly characteristics, and the availability of the raw material, its utilization as a structural platform for flexible green electronics is anticipated.